Prevalence and factors associated with conjugal violence (Research, Society and Development, 2020)
Objective: to investigate the prevalence and factors associated with domestic violence among women users of nine units of the basic attention to health of Maceió-Al. Methodology: Quantitative, exploratory, cross-sectional and descriptive study.cross-sectional. Conducted in in nine basic health units in the eight health districts in the city of Maceió-Al. Participated in the research 247 women users of nine primary health care units, living in the city of Maceió - Al, aged between 18 and 49 years old. It was used the instrument Abuse Assesment Screen (AAS) for detection of violence and a structured form to characterize the socio-demographic data of the interviewees. Results: among the 247 interviewed, was detected 43.72% prevalence of domestic violence. There was a significant association between physical violence with family income and the partner's age, smoking, alcohol use and violence during childhood. Conclusion: the data showed high prevalence of domestic violence in your most practiced by intimate partner. It is necessary to greater investments in training with the pros of the basic health units to recognize and deal with domestic violence.